Distance-dependent inhibition facilitates focality of gamma oscillations in the dentate gyrus - Michael Strüber (Nature Portfolio, 2017)
Perisomatic-inhibitory interneurons (PIIs) contribute to the generation of gamma oscillations in the hippocampus. Here the authors demonstrate distance-dependent inhibition between PIIs in freely moving mice, and use computational analysis to show that distance-dependent inhibition supports the emergence of focal gamma bursts.